2012
DOI: 10.1515/plm-2012-0004
|View full text |Cite
|
Sign up to set email alerts
|

Equine wound healing: influence of low level laser therapy on an equine metacarpal wound healing model

Abstract: Objective: To evaluate the effects of low level laser therapy (LLLT) on healing of full thickness symmetrical skin wounds in horses. LLLT is a therapeutic modality using the application of light, usually a low power laser or light emitting diode in the power range of 1 mW to 12 W that, in practical terms, promotes tissue regeneration as well as reducing infl ammation and pain. Study design: Experimental study. Animals: Healthy horses (n = 8). Methods: Full thickness, 2.5 cm square skin wounds were created in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In their study conducted in New Zealand, Meredith et al (2001) found that physiotherapy was the second most common method of health promotion in sport horses, and used most often (in 36% of cases) in the jumping horses. The beneficial effect of LLLT on wound healing in horses was confirmed by Jann et al (2012), who exposed a surgical skin wound of the dorsal surface of the metacarpal region to radiation. Laser radiation of a wavelength of 635 nm was applied at 5.1 J/cm 2 in eight mares.…”
Section: Equine Veterinary Medicinementioning
confidence: 93%
“…In their study conducted in New Zealand, Meredith et al (2001) found that physiotherapy was the second most common method of health promotion in sport horses, and used most often (in 36% of cases) in the jumping horses. The beneficial effect of LLLT on wound healing in horses was confirmed by Jann et al (2012), who exposed a surgical skin wound of the dorsal surface of the metacarpal region to radiation. Laser radiation of a wavelength of 635 nm was applied at 5.1 J/cm 2 in eight mares.…”
Section: Equine Veterinary Medicinementioning
confidence: 93%
“…Only two studies using LLLT for the healing of an open wound were identified in equines (see Table 5). In a study conducted by Jann et al, 8 horses received a single 2.5cm square wound on the mid-metacarpal region of one leg [35]. The horses were randomly split into control and laser-treated groups.…”
Section: Equinementioning
confidence: 99%
“…The horses were randomly split into control and laser-treated groups. A dual diode laser system with a wavelength of 635 nm and an energy density of 5.1 J/cm 2 was used every other day for five minutes for a total of 80 days [35]. The rate of wound healing and a histological evaluation which consisted of the formation of granulation tissue, ulceration, inflammation, and presence of inflammatory cells were examined.…”
Section: Equinementioning
confidence: 99%
“…Despite overall inconsistent methodologies in numerous in vitro and in vivo studies evaluating laser therapy, findings indicate that LLLT can improve healing time in mammals [ 28 30 ]. Specifically, LLLT accelerated wound healing in rats, mice, pigs, horses, dogs, and humans [ 29 , 31 35 ]. Given the complexities of wound care in captive amphibians, LLLT may represent a valuable noninvasive wound management tool.…”
Section: Introductionmentioning
confidence: 99%